2016
DOI: 10.1002/eji.201646401
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal NLRP10 contributes to contact hypersensitivity responses in mice

Abstract: The nucleotide binding and oligomerization domain-like receptor (NLR) protein NLRP10 is highly expressed in the epidermis and contributes to cell-autonomous responses against invasive bacteria. To investigate the role of NLRP10 in inflammatory responses of the skin we analyzed the effect of full-body and keratinocyte-specific depletion of NLRP10 in croton oil-induced irritant contact dermatitis (ICD) and 1-fluoro-2,4-dinitrobenzene (DNFB)-induced contact hypersensitivity (CHS) in mice. Nlrp10 −/− mice were phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
(58 reference statements)
2
20
0
Order By: Relevance
“…However, in the current study, we did not observe any increase in caspase-1 activation or IL-1b production in PYNOD-KO macrophages in response to inflammasome activators or microbial infection. Our current results are consistent with recent reports (6) and suggest that the basal PYNOD expression in macrophages is not essential for determining the magnitude of these responses. The apparent discrepancy of our previous and current results can be explained by the presence of redundant regulatory mechanisms for caspase-1 activation (18,19).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, in the current study, we did not observe any increase in caspase-1 activation or IL-1b production in PYNOD-KO macrophages in response to inflammasome activators or microbial infection. Our current results are consistent with recent reports (6) and suggest that the basal PYNOD expression in macrophages is not essential for determining the magnitude of these responses. The apparent discrepancy of our previous and current results can be explained by the presence of redundant regulatory mechanisms for caspase-1 activation (18,19).…”
Section: Discussionsupporting
confidence: 83%
“…The basal expression of PYNOD in human skin is also high (23). Recently, Damm et al (6) reported that total and epidermis-specific PYNOD-KO mice exhibit defects in the T cell-mediated inflammatory response using the DNFB-induced CHS model. They also observed a significant reduction in T cell infiltration in the inflamed ear skin of the total but not the epidermal-specific PYNOD-KO mice in this model, suggesting that the epidermal and nonepidermal PYNOD contribute to CHS by different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOD‐like receptor family pyrin domain containing 10 (NLRP10), which lacks the leucine‐rich domain present in pro‐inflammatory NLRPs, inhibits inflammation and is predominantly expressed in terminally differentiated keratinocytes (Figure , right panel; Figure ) . Knockout of NLRP10 did not impair epidermal cornification but reduced contact hypersensitivity responses in mice . Interestingly, caspase‐14 and gasdermin A are further keratinocyte differentiation‐specific proteins that are closely related to pyroptosis factors.…”
Section: Epidermal Keratinocytes Suppress Inflammation During Normal mentioning
confidence: 99%
“…[33] Knockout of NLRP10 did not impair epidermal cornification but reduced contact hypersensitivity responses in mice. [49] Interestingly, caspase-14 [50][51][52] and gasdermin A [33][34][35][36]53] are further keratinocyte differentiation-specific proteins that are closely related to pyroptosis factors. Caspase-14 has evolved from caspase-1 and caspase-15 [52] but in contrast to those lacks a CARD or pyrin domain.…”
Section: Epidermal Ker Atino C Y Te S Suppre Ss Infl Ammation Durinmentioning
confidence: 99%